Détresse respiratoire suite à une intoxication domestique au chlore - Benhamza, Sabah (Anesthésie & Réanimation, 2021)
The COVID-19 is responsible for home confinement in our country, creating an anxious atmosphere and a significant use of detergents, which oftenleads to involuntary intoxications. We report a case of chlorine poisoning caused by repeated mixing of bleach with vinegar.